Döntéselmélet és erkölcsi normák - Huoranszki, Ferenc (Szociológiai Szemle, 2024)
The relationship between the theory of rational decisions and the role of the moral observance of norm, played in the explanation of action, is a problematic one. The reason is that a considerable part of social scientists and philosophers use such a model of the theory of rational decisions, canonised by Leonard Savage, in which action can only have a derived value. This model is linked to the interpretation of action, elaborated by Hume and Kant, and the subsequent philosophical tradition. However, this variant of the theory of decision-making gives an adequate picture of the logical structure of pre-decision considerations only if certain conditions are met. However, there is such a variant of the theory of decision making, elaborated by Richard Jeffrey, which is able to consider the fact that the rational actor assesses not only the consequences of his actions, but also the action itself. This variant of the theory of decision-making makes it possible to understand how the moral norms, as motivating forces are located at the logical space of pre-action considerations.